Developmental stress and birdsong: integrating signal function and development. (December 2015) - MacDougall-Shackleton, Scott A
Highlights: Developmental stress impairs song in species with complex songs. Evidence for this hypothesis is mixed in domesticated songbirds. Experimental stressors vary in ecological validity and experimental control. It is unclear if song reflects early environment or developmental resilience. Song appears to reflect developmental trade-offs rather than phenotypic programming. Abstract : The developmental stress hypothesis proposes that birdsong reflects developmental experience and thus correlates with other traits. There is evidence that developmental stressors impair song development in wild songbirds with sexually selected songs, but the evidence from domesticated species is mixed. Studies vary in emphasizing ecological validity or experimental control, which may contribute to mixed results. Although phenotypic programming is a dominant concept in developmental phenotypic plasticity, birdsong appears to develop as a result of tradeoffs rather than phenotype matching. Further work needs to more explicitly address trade-offs by quantifying which traits are traded-off with song during development. A better understanding of physiological mechanisms of these processes is also needed to elucidate how song may indicate other aspects of a bird's phenotype.